Using Asynchronous Discussion for Teaching and Learning in EFL Class During Pandemic - Aras, Muhammad Sahrir; Ybnu T, Muhammad (Yayasan Cendekiawan Indonesia Timur, 2022)
This research aims at investigating the students’ perception on the use of asynchronous discussion for teaching and learning in EFL class during pandemic. This research is a descriptive qualitative research. This research was conducted at STKIP Tomakaka Tiwikrama Pasangkayu. The data was collected through observation and interview. The data was analyzed by using Interactive Analysis model. The result of the research shows that most of the students were pleased with the asynchronous discussion format. The students believe that the asynchronous discussion is used effectively for teaching and learning in EFL class during pandemic. Additionally, the process of sharing information between students during the discussion allows them to improve their knowledge and eradicate misconception. The eradication of misconception was done through several phases: ideas exchange, evaluation of own belief, and reconstruction of new belief.